In vitro antibacterial activity of Curcuma longa (Zingiberaceae) against nosocomial bacteria in Montería, Colombia - Méndez Álvarez, Nelson (2016)
Bacterial resistance is a growing health problem worldwide that has serious economic and social impacts, compromising public health, and the therapeutic action of current antibiotics. Therefore, the search for new compounds with antimicrobial properties is relevant in modern studies, particularly against bacteria of clinical interest. In the present study, in vitro antibacterial activity of the ethanol extract and essential oil of Curcuma longa (Zingiberaceae) was evaluated against nosocomial bacteria, using the microdilution method. Escherichia coli strains, Pseudomonas aeruginosa, Klebsiella pneumoniae, Proteus sp. were used, Salmonella sp. and Bacillus sp., isolated from nosocomial infections in a hospital in the city of Monteria and reference strains of S. aureus ATCC 43300, S. aureus ATCC 29213, S. aureus ATCC 25923, P. aeruginosa ATCC 27853, E. coli ATCC 25922 and K. pneumonia ATCC 700603. The ethanol extract antibacterial profile was more efficient at higher concentrations (1 000 ppm), obtaining significant percentages of reduction of more than 50 % against K. pneumoniae ATCC 700603 and a clinical isolate of E. coli; while compared to Bacillus clinical isolate, was more active than the essential oil. For the rest of microorganisms, the reduction percentages obtained at a concentration of 1 000 ppm varied between 17 and 42 % with ethanolic extract, and 8 to 43 % with essential oil. At concentrations of 100 and 500 ppm antibacterial activity of the extracts was lower. The results indicated that the ethanolic extract and essential oil of C. longa rhizomes have active compounds with antibacterial properties that could be used in future research as a therapeutic alternative for the treatment of infections caused by nosocomial pathogens.